Micro‐Gel Ensembles for Accelerated Healing of Chronic Wound via pH Regulation. Issue 22 (21st May 2022) - Cui, Tingting; Yu, Jiafei; Wang, Cai‐Feng; Chen, Su; Li, Qing; Guo, Kun; Qing, Renkun; Wang, Gefei; Ren, Jianan
Abstract: The pH value in the wound milieu plays a key role in cellular processes and cell cycle processes involved in the process of wound healing. Here, a microfluidic assembly technique is employed to fabricate micro‐gel ensembles that can precisely tune the pH value of wound surface and accelerate wound healing. The micro‐gel ensembles consist of poly (hydroxypropyl acrylate‐ co ‐acrylic acid)‐magnesium ions (poly‐(HPA‐ co ‐AA)‐Mg 2+ ) gel and carboxymethyl chitosan (CMCS) gel, which can release and absorb hydrogen ion (H + ) separately at different stages of healing in response to the evolution of wound microenvironment. By regulating the wound pH to affect the proliferation and migration of cell on the wound and the activity of various biological factors in the wound, the physiological processes are greatly facilitated which results in much accelerated healing of chronic wound. This work presents an effective strategy in designing wound healing materials with vast potentials for chronic wound management. Abstract : Micro‐gel ensembles are developed to allow continuous and intelligent regulation on wound microenvironment pH over the four healing phases of hemostasis, inflammation, hyperplasia, and remodeling, which can effectively promote the formation of new blood vessels, the proliferation and migration of fibroblasts and adipocytes, and the polarization of macrophages, and ultimately accelerate wound healing.